An Election of Self-Centered Tweets: Analysis of Twitter Usage in the 2016 São Paulo Mayoral Election - Chicarino, Tathiana Senne; Penteado, Claudio; Bachini, Natasha; Malina, Pedro; Lobo, Denis Carneiro (Pontifícia Universidade Católica de São Paulo, 2018)
In order to observe the uses of Twitter in the 2016 São Paulo mayoral election, this article presents a predominantly quantitative analysis of the digital campaigns carried out by the main candidates Celso Russomano (PRB); Fernando Haddad (PT); João Dória (PSDB); Luiza Erundina (PSOL); Marta Suplicy (PMDB); Major Olímpio (SD) and Ricardo Young (REDE). Researchers from  NEAMP (PUC/SP - Brazil) and DMRC (QUT - Australia) combined Big Data analysis techniques to verify the continuities and innovations in two main variables: (1) the current digital campaign strategies compared to previous ones and (2) the candidates/followers interactions. The results pointed to a correlation between the broadening of political issue debate on social media and the increase of personalistic contents along with the reduction of the candidate/follower interactive dialogues.